2016
DOI: 10.1186/s12910-016-0115-3
|View full text |Cite
|
Sign up to set email alerts
|

Heed or disregard a cancer patient’s critical blogging? An experimental study of two different framing strategies

Abstract: BackgroundWe have examined healthcare staff attitudes of toward a blogging cancer patient who publishes critical posts about her treatment and their possible effect on patient-staff relationships and treatment decisions.MethodsWe used two versions of a questionnaire containing a vignette based on a modified real case involving a 39-year-old cancer patient who complained on her blog about how she was encountered and the treatment she received. Initially she was not offered a new, and expensive treatment, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…However, information posted on blogs and discussion forums, especially anonymous posts, showed significantly lower levels of scientific accuracy compared to other electronic resources. According to a Swedish study [ 26 ], the healthcare personnel can also be subjectively influenced by the reading of a patient’s critical blog. In this study, the authors showed that staff exhibiting a neutral, professional and pragmatic attitude is more inclined to heed and respond to critic patients [ 26 ].…”
Section: Reviewmentioning
confidence: 99%
“…However, information posted on blogs and discussion forums, especially anonymous posts, showed significantly lower levels of scientific accuracy compared to other electronic resources. According to a Swedish study [ 26 ], the healthcare personnel can also be subjectively influenced by the reading of a patient’s critical blog. In this study, the authors showed that staff exhibiting a neutral, professional and pragmatic attitude is more inclined to heed and respond to critic patients [ 26 ].…”
Section: Reviewmentioning
confidence: 99%
“…In this context, the quality of the cancer patients’ encounters with healthcare professionals might be considered as of relatively minor importance [6]. Nevertheless, several studies indicate that experiences of respectful encounters with healthcare professionals may result in patients feeling strengthened and encouraged, both among cancer patients and others [79], and patients’ experiences of disrespectful or wrongful encounters may have negative consequences for their health and their trust in the healthcare system [911].…”
Section: Introductionmentioning
confidence: 99%
“…Previously conducted studies have, however, indicated that Swedish physicians actually hold values that are in conflict with official values. [9][10][11][12][13][14][15][16][17][18] By official values in health care, we mean the values expressed in health care law and regulations. However, personal values that are at odds with the official values are seldom openly declared by the physician.…”
Section: Introductionmentioning
confidence: 99%
“…The simple idea is that the physician's personal values remain tacit while affecting factual judgements, so that the practical conclusion about what to do as a health care professional is informed by these values. [9][10][11][12][13][14][15][16][17][18][19] Value impregnation of factual aspects is not a phenomenon unique to Sweden or Swedish health care. In a Swiss study, Hermann et al investigate physicians' decision-making process regarding assisted suicide, claiming that physicians' personal values enter 'through the back-door' as they colour the assessment of patients' decision-making capacity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation